1996
DOI: 10.1016/s1074-5521(96)90079-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial resistance to vancomycin: five genes and one missing hydrogen bond tell the story

Abstract: A plasmid-borne transposon encodes enzymes and regulator proteins that confer resistance of enterococcal bacteria to the antibiotic vancomycin. Purification and characterization of individual proteins encoded by this operon has helped to elucidate the molecular basis of vancomycin resistance. This new understanding provides opportunities for intervention to reverse resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
259
0
7

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(269 citation statements)
references
References 31 publications
3
259
0
7
Order By: Relevance
“…[11,[21][22][23][24] This alteration amountst ot he replacement of an amide bond by an ester linkage,t hereby eliminating one of the key hydrogen bonds, and greatly decreasing the binding affinity of 1 to DADLacr elative to DADA. [25][26][27] Several promising approaches have been developedt o counter the risk of widespread infection, [28] with much emphasis devoted towards the development of vancomycina nalogues;o ften through chemical modification.…”
mentioning
confidence: 99%
“…[11,[21][22][23][24] This alteration amountst ot he replacement of an amide bond by an ester linkage,t hereby eliminating one of the key hydrogen bonds, and greatly decreasing the binding affinity of 1 to DADLacr elative to DADA. [25][26][27] Several promising approaches have been developedt o counter the risk of widespread infection, [28] with much emphasis devoted towards the development of vancomycina nalogues;o ften through chemical modification.…”
mentioning
confidence: 99%
“…For this reason, it was originally suggested that pathogens might never acquire resistance to vancomycin because it would require them to remodel the peptidoglycan biosynthetic pathway itself. In the late 1980s, however, the first clinical isolates of VRE appeared and were found to reprogram cell wall biosynthesis such that the pendant pentapeptide of peptidoglycan precursors terminated in D-alanyl-D-lactate (D-Ala-D-Lac), rather than in D-Ala-D-Ala (7)(8)(9)(10)(11)(12). The affinity of vancomycin for precursors terminating in D-Ala-D-Lac is ϳ1000-fold lower than for precursors terminating D-Ala-D-Ala We have shown previously that the non-pathogen Streptomyces coelicolor carries a gene cluster conferring inducible, high-level resistance to vancomycin (13).…”
mentioning
confidence: 99%
“…The emergence of vancomycin resistance in the last decade has caused considerable concern because this drug is widely used to treat methicillin-resistant Gram-positive infections and there are few alternatives to it. The most common forms of resistance to vancomycin occur in enterococcal strains and involve the acquisition of a set of genes encoding proteins that direct peptidoglycan precursors to incorporate D-Ala-D-Lac (Lac ϭ lactate) instead of D-Ala-D-Ala (3,4). Because vancomycin does not bind D-Ala-D-Lac (Fig.…”
mentioning
confidence: 99%